The feasibility of Sorghum (Sorghum vulgare) fodder as poultry feed ingredients seen from growth performance, nutrient content and fiber profile of Sorghum fodder (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: The aim of the study was to assess the feasibility of fodder Sorghum as poultry feed in terms of growth performance (plant height and fresh weight), nutritional quality (moisture, ash, crude protein, extract ether, crude fiber, extract material without nitrogen, and metabolic energy), and scanning electron microscopy energy dispersive X-ray (SEM-EDX). Materials and Methods: The study used a completely randomized design with six treatments and three replications. The treatments consisted of planting times of 24, 48, 72, 120, and 240 h and a control (0 h). Results: The results showed that there was a significant effect (p ≤ 0.05) when planting Sorghum fodder (SGF) on growth performance and moisture, but it had no significant effect on fresh weight, ash, crude protein, extract ether, crude fiber, nitrogen-free extract, energy metabolic aspects, and SEM-EDX. Conclusion: SGF is suitable as a feed ingredient for poultry in terms of nutrition and contains ZrO2, which functions as an antifungal.J. Adv. Vet. Anim. Res., 10(2): 222–227, June 2023http://doi.org/10.5455/javar.2023.j672